Study on the inhibition activity and mechanism of Tanreqing against Klebsiella pneumoniae biofilm formation in vitro and in vivo - Zhang, Wenxia; He, Min; Kong, Nana; Niu, Yuxiao; Li, Anhong; Yan, Yuzhong (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: To evaluate the antibacterial effect of Tanreqing (TRQ) against K. pneumoniae and its inhibition activity on bacterial biofilm formation in vitro and in vivo, and to explore the mechanism of the inhibitory effects of TRQ on K. pneumoniae biofilm formation.An in vitro biofilm model of K. pneumoniae was established, and the impact of TRQ on biofilm formation was evaluated using crystal violet staining and scanning electron microscopy (SEM). Furthermore, the clearance effect of TRQ against K. pneumoniae in the biofilm was assessed using the viable plate counting method; q-RT PCR was used to evaluate the inhibitory effect of different concentrations of TRQ on the expression of biofilm-related genes in Klebsiella pneumoniae; The activity of quorum sensing signal molecule AI-2 was detected by Vibrio harveyi bioluminescence assay; Meanwhile, a guinea pig lung infection model of Klebsiella pneumoniae was constructed, and after treated with drugs, pathological analysis of lung tissue and determination of bacterial load in lung tissue were performed. The treatment groups included TRQ group, imipenem(IPM) group, TRQ+IPM group, and sterile saline group as the control.The formation of K. pneumoniae biofilm was significantly inhibited by TRQ in vitro experiments. Furthermore, when combined with IPM, the clearance of K. pneumoniae in the biofilm was notably increased compared to the TRQ group and IPM group alone. q-RT PCR analysis revealed that TRQ down-regulated the expression of genes related to biofilm formation in K. pneumoniae, specifically luxS, wbbm, wzm, and lsrK, and also inhibited the activity of AI-2 molecules in the bacterium. In vivo experiments demonstrated that TRQ effectively treated guinea pig lung infections, resulting in reduced lung inflammation.Additionally, when combined with IPM, there was a significant reduction in the bacterial load in lung tissue.Conclusion: TRQ as a potential therapeutic agent plays a great role in the treatment of K. pneumoniae infections, particularly in combination with conventional antibiotics. And TRQ can enhanced the clearance effect on the bacterium by inhibiting the K. pneumoniae biofilm formation, which provided experimental evidence in support of clinical treatment of TRQ against K. pneumoniae infections.